Electrical properties of field-effect transistor with interlinked ZnO tetrapod network as an active layer - Witawat Ponhan (2018)
© 2016 Elsevier B.V. In this work, we have investigated the thin film based field-effect transistor (FET) with interlinked ZnO tetrapod network (ITN-ZnO) used as an active channel layer. The ITN-ZnOs were synthesized by microwave assisted thermal oxidation technique. A ZnO FET with bottom gate structure was fabricated and investigated in terms of electrical properties. X-ray diffraction pattern revealed the wurtzite hexagonal structure of the ITN-ZnO. A drain current on/off ratio of 104, the off-state current as low as 10 nA, the threshold voltage of 10 V, field effect mobility of 7.939 cm2/Vs and sub-threshold swing of 1.4 V/decade were obtained. These results suggested that ITN-ZnO could be applied for FET, which could be operated in an enhancement mode.